Nias Tribe Tradition as an Ideas in Creating Painting - Telaumbanua, Calvin Galileo; Ruta, I Made; Karja, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2024)
The Maena dance, a cultural heritage from the Nias tribe on Nias Island, North Sumatra, Indonesia, is a traditional dance full of meaning and cultural values. This dance displays strong and dynamic movements, with dancers wearing traditional Nias clothing. Accompanying music, such as gondang, taganing, and tifa, creates a rhythm that strengthens the expression of the dance. The Maena dance depicts the strength, enthusiasm and unity of the Nias people. In this dance, vigorous war movements, high jumps symbolize courage, and expressive hand and eye movements express a variety of emotions. This dance is also used in various traditional ceremonies, cultural celebrations, and important moments in the lives of the Nias people. The Maena dance, as a source of creative ideas, inspires us to dig deeper into the cultural values and spirit of courage contained in this dance. Combining elements of Maena dance with modern art or developing new dances could provide a unique creative platform, celebrating Nias' cultural heritage while presenting a message of strength, unity and courage to today's generation.